Methodological challenges in nature-culture and environmental history research
1 online resource
Keywords: This book examines the challenges and possibilities of conducting cultural environmental history research today. Disciplinary commitments certainly influence the questions scholars ask and the ways they seek out answers, but some methodological challenges go beyond the boundaries of any one discipline. The book examines: how to account for the fact that humans are not the only actors in history yet dominate archival records; how to attend to the non-visual senses when traditional sources offer only a two-dimensional, non-sensory version of the past; how to decolonize research in and beyond the archives; and how effectively to use sources and means of communication made available in the digital age. This book will be a valuable resource for those interested in environmental history and politics, sustainable development and historical geography.